Airway anastomosis for lung transplantation - Anile, Marco (J Thorac Dis, 2016)
Lung transplantation (LT) is the only viable option for a selected group of patients with end stage pulmonary diseases. During the recent years satisfactory results in terms of long-term survival and quality of life have been achieved with improvements in surgical technique, immunosuppression and perioperative management. Since the beginning, the airway anastomosis has been considered crucial and significant efforts have been made to understand the healing process. A number of experimental studies allowed improving the surgical technique by modifying the technique of suturing, the anastomotic protection and type and dose of immunosuppression, reducing the risk of airway complications. Furthermore, a huge progress has been made in the management of such complications. Early diagnosis of bronchial complications and their prompt and correct management are crucial to achieve long-term survival.